Analisis Kebutuhan Pengembangan Model Pembelajaran Geografi Berbasis Lingkungan - Marni Marni (FKIP Universitas Palangka Raya, 2023)
The background of this research begins with the demands of professional teachers in carrying out the mandate to create creative and productive learning by actively involving students. A creative and productive learning process will be able to create a fun learning atmosphere for students. Geography teachers who want fun learning must master the application of environment-based learning models. This research is a preliminary study in the form of needs analysis in developing an environment-based geography learning model to create a fun school. Needs analysis was carried out to determine the level of understanding of geography teachers in Palangkaraya City regarding the application of an environment-based learning model. The main problem he faced was the low learning motivation of students participating in geography lessons. On the other hand, teachers have difficulty utilizing the environment as the main learning resource. This research is the first part of a series of Research and Development models. In this preliminary study, researchers need data on perceptions, skills, and curriculum suitability related to the application of an environment-based geography learning model to create a fun school. The method used is filling out a questionnaire and Focus Group Discussion (FGD). The research subjects were geography teachers in Palangkaraya City. The results of the study concluded that the teacher's perception regarding the concept of developing an environment-based geography learning model was good. The teacher provides information support regarding the level of understanding of the application of the environment-based learning model based on the experiences experienced during teaching. The teacher's skills in the practice of implementing the environment-based geography learning model are quite good, but there are still those who have not applied them according to procedures or syntax in a systematic manner. This has an impact on the learning process that is not interesting for students. Utilization of the environment as a learning resource is able to answer the demands of implementing a scientific approach in the 2013 curriculum. However, most teachers still experience confusion in collaborating geography subject matter with the natural environment around the school.